Lower Circulating Irisin Level in Patients with Diabetes Mellitus: A Systematic Review and Meta-Analysis - Du, X.-l.; Jiang, W.-x.; Lv, Z.-t. (Hormone and Metabolic Research, 2016)
Studies measuring circulating irisin levels in patients with insulin resistance conditions such as type 2 diabetes mellitus (T2DM) and gestational diabetes mellitus (GDM) have achieved controversial results. Our systematic review and meta-analysis aim to assess the circulating irisin levels in patients with diabetes mellitus. Pubmed, EMBASE, CENTRAL, ISI Web of Science, and CNKI were searched to identify observational studies of circulating irisin levels in patients with diabetes mellitus. Two reviewers independently searched the databases and screened studies according to the inclusion criteria. Data were extracted using a standardized collection form. Meta-analysis was performed. A total of 23 studies (17 cross-sectional and 6 case control) involving 1 745 diabetic patients and 1 337 non-diabetic controls were selected. Compared with non-diabetic controls, circulating irisin concentrations were significantly lower in patients with T2DM (SMD −1.72, 95%CI −2.49, −0.96; p<0.00001) and GDM (SMD −0.76, 95CI −1.31, −0.22; p=0.006), but 30 percent higher in patients with T1DM. Circulating irisin in Asian diabetic patients decreased more than European patients. The findings of our current review suggest that circulating irisin levels were decreased in patients with T2DM and GDM, but not in patients with T1DM.
Keywords: irisin; type 2 diabetes mellitus; gestational diabetes mellitus; systematic review